Totaliproductive Maintenance (Tpm) Analysis Using the Overall Equipment Effectiveness (Oee) Method and Six Big Losses on an Injection Molding Machine - Mokhamad Ridloi; Ribangun Bamban Jakaria (Universitas Muhammadiyah Sidoarjo, 2021)
. PT. XYZ is a manufacturing companyjthat produces a variety of materials from plastics, this company cangnot be separated from problems relatedhto the effectiveness of machinery / equipment. The problem that is experienced today is that there is a lot of damage to the injection moulding machine that has decreased speed as a result of the damage to the number of defect parts because the machine often experiences breakdown. Data collection is conducted with structured observations and interviews. To solve the problem that occurs, done a machine maintenance or maintenance by means of measurement using the method of Total Productive Maintenance which includes Overall Equipment Effectiveness and Six Big Losses. This study aims to determine the level of equipment total production process, to determine the factors causing the valuenof overall equipment Efectivenees (OEE) low and identify losses that occur with the standard value of